Kontribusi Pola Asuh Orang Tua Dan Lingkungan Teman Sebaya Terhadap Displin Belajar Siswa Di SD Islam Al-A’laa Kecamatan Pamijahan Kabupaten Bogor - Indah Pratiwi; M. Zainal Arifin; Samsul Huda (Primer Edukasi Journal, 2022)
The aim of this research is to determine the influence of parental parenting on student learning discipline, the influence of the peer environment on student learning discipline, the influence of parental parenting and the peer environment together on student learning discipline. The data collection technique used a questionnaire for fifth grade students at Al-A'laa Islamic Elementary School, Pamijahan District, Bogor Regency in 2020 with a sample size of 21 students. This study uses a quantitative approach. The results of the research show that: 1) Parental parenting has an influence but is not significant on the learning discipline of fifth grade students at Al-A'laa Islamic Elementary School. Al-A'laa Islamic Elementary School. 2) The peer environment has a significant influence on the learning discipline of fifth grade students at Al-a'laa Islamic Elementary School. 3) The parenting style of parents and the peer environment together have a significant influence on the learning discipline of fifth grade students at Al-A'laa Islamic Elementary School